Identification and profiling of conserved and novel microRNAs in Laodelphax striatellus in response to rice black-streaked dwarf virus (RBSDV) infection - Li, Jun-Min (Genom Data, 2014)
MicroRNAs (miRNAs) are small non-coding endogenous RNA molecules that play important roles in various biological processes. This study examined microRNA profiles of Laodelphax striatellus using the small RNA libraries derived from virus free (VF) and rice black-streaked dwarf virus (RBSDV) infected (RB) insects. A total of 59 mature miRNAs (46 miRNA families) were identified as conserved insect miRNAs in both VF and RB libraries. Among these conserved miRNAs, 24 were derived from the two arms of 12 miRNA precursors. Nine conserved L. striatellus miRNAs were up-regulated and 12 were down-regulated in response to RBSDV infection. In addition, a total of 20 potential novel miRNA candidates were predicted in the VF and RB libraries. The miRNA transcriptome profiles and the identification of L. striatellus miRNAs differentially expressed in response to RBSDV infection will contribute to future studies to elucidate the complex miRNA-mediated regulatory network activated by pathogen challenge in insect vectors.